Pengenalan Masakan Tradisional Indonesia Menggunakan Game Edukasi Roblox - Axellio Felix Tjandra; Robby Kurniawan Budhi; Yonatan Widianto (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to develop an educational game for cooking traditional Indonesian cuisine based on Roblox Studio as an interactive learning medium that is able to attract the attention and interest of the younger generation. This game is designed not only as a means of entertainment, but also as an educational medium that introduces the culinary richness of the archipelago through a simulation of the cooking process that collapses and resembles real cooking steps. Three traditional dishes were chosen as the main focus in this game, namely Rawon Ponorogo, Soto Makassar, and Minangkabau Rendang. The three dishes were chosen because they have different tastes, cooking techniques, and cultural characteristics, so that players can understand that traditional Indonesian food is rich in variety and historical value. The development method used is the Waterfall method, which includes the stages of analyzing user and system needs, designing the interface and game mechanics, implementing using the Lua programming language in Roblox Studio, testing the game's functionality, and evaluating the results through the distribution of questionnaires to users. This game makes use of various interactive elements such as ProximityPrompt to trigger player actions, GUI Progress Bar as an indicator of the cooking process, Timer to set a time limit according to the difficulty level, and a Teleport system between stages to guide the gameplay. The existence of a different time limit system at each stage (10 seconds, 5 seconds, and 3 seconds) provides a challenge that can increase the player's concentration in following the correct cooking steps. The test results show that the game can run well and can be played easily by novice users. Based on the results of the questionnaire, users stated that this game is visually appealing, easy to understand, and effective in introducing Indonesian culinary culture. Therefore, this game functions as a creative digital learning medium in preserving the culinary of the archipelago.